PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA SERTA KOMPENSASI TERHADAP SEMANGAT KERJA KARYAWAN - Daud, Dominicus Savio Febian; Salit Ketut Netra, I Gusti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Work Spirit is the attitude and willingness that exists in employees in doing work with a happy state in order to get maximum results. Facing today's tight business competition, of course, companies need high morale for every employee. The purpose of this study was to analyze the effect of the work environment and work motivation and compensation on Work Spirit of PT Danamas Insan Kreasi Andalan Cabang Denpasar. The number of samples used was 120 employees of the sales division for opening online accounts with probability sampling method with Simple Random Sampling technique. Data was collected by means of a questionnaire. The data were analyzed using multiple linear regression analysis techniques. In this study using Maslow's Hierarchy of Needs Theory. The results of the study show that the work environment has a positive and significant effect on work spirit  of PT Danamas Insan Kreasi Andalan Cabang Denpasar. Work motivation has a positive and significant effect on work spirit at PT Danamas Insan Kreasi Andalan Cabang Denpasar. Compensation has a positive and significant effect on work spirit at PT Danamas Insan Kreasi Andalan Cabang Denpasar